Extraction of Rutin from the Leaf of Male Carica papaya Linn. using Microwave-Assisted and Ultrasound-Assisted Extractive Methods - See Khai Chew; Wen Hui Teoh; Sok Lai Hong; Rozita Yusoff (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
Açıkel, Ü., Erşan, M., & Sağ Açıkel, Y. 2010. Optimization of critical medium components using response surface methodology for lipase production by Rhizopus delemar. Food and Bioproducts Processing, 88(1), 31-39. doi: https:// doi.org/10.1016/j.fbp.2009.08.003Carniel, N., Dallago, R. M., Dariva, C., Bender, J. P., Nunes, A. L., Zanella, O., . . . Luiz Priamo, W. 2017. Microwave‐assisted extraction of phenolic acids and flavonoids from Physalis angulata. Journal of Food Process Engineering, 40(3), e12433.Chahyadi, A., & Elfahmi. 2020. The influence of extraction methods on rutin yield of cassava leaves (Manihot esculenta Crantz). Saudi pharmaceutical journal, 28(11), 1466-1473. doi: https:// doi.org/10.1016/j.jsps.2020.09.012De Luna, S. L. R., Ramírez-Garza, R., & Saldívar, S. O. S. 2020. Environmentally Friendly Methods for Flavonoid Extraction from Plant Material: Impact of Their Operating Conditions on Yield and Antioxidant Properties. The Scientific World Journal, 2020.Ferreira, S. C., Bruns, R., Ferreira, H., Matos, G., David, J., Brandão, G., . . . Souza, A. 2007. Box-Behnken design: an alternative for the optimization of analytical methods. Analytica chimica acta, 597(2), 179-186.He, Q., Li, Y., Zhang, P., Zhang, A., & Wu, H. 2016. Optimisation of microwave-assisted extraction of flavonoids and phenolics from celery (Apium graveolens L.) leaves by response surface methodology. Czech Journal of Food Sciences, 34(4), 341-349.Hyun, S. B., Ko, M. N., & Hyun, C.-G. 2021. Carica papaya leaf water extract promotes innate immune response via mapk signaling pathways. Journal of Applied Biological Chemistry, 64(3), 277-284.Khadam, S., Afzal, U., Gul, H., Hira, S., Satti, M., Yaqub, A., . . . Gulfraz, M. 2019. Phytochemical screening and bioactivity assessment of leaves and fruits extract of Carica papaya. Pakistan journal of pharmaceutical sciences, 32(5).Latiff, N., Ong, P. Y., Abdullah, L. C., Abd Rashid, S. N. A., Fauzi, N. A. M., & Amin, N. A. M. 2021. Ultrasonic-Assisted Extraction (UAE) for Enhanced Recovery of Bioactive Phenolic Compounds From Cosmos Caudatus Leaves.Li, Y., Radoiu, M., Fabiano-Tixier, A.-S., & Chemat, F. 2013. From Laboratory to Industry: Scale-up of Microwave-Assisted Reactors, Quality and Safety Consideration for Microwave-Assisted Extraction. In (pp. 207-229).Ling, Y. Y., Fun, P. S., Yeop, A., Yusoff, M. M., & Gimbun, J. 2019. Assessment of maceration, ultrasonic and microwave assisted extraction for total phenolic content, total flavonoid content and kaempferol yield from Cassia alata via microstructures analysis. Materials Today: Proceedings, 19, 1273-1279.Liu, H.-L., Lan, Y.-W., & Cheng, Y.-C. 2004. Optimal production of sulphuric acid by Thiobacillus thiooxidans using response surface methodology. Process Biochemistry, 39(12), 1953-1961. doi: https://doi.org/10.1016/j.procbio.2003.09.018Liu, Y., Wei, S., & Liao, M. 2013. Optimization of ultrasonic extraction of phenolic compounds from Euryale ferox seed shells using response surface methodology. Industrial Crops and Products, 49, 837-843.Lu, X., Zheng, Z., Li, H., Cao, R., Zheng, Y., Yu, H., . . . Zheng, B. 2017. Optimization of ultrasonic-microwave assisted extraction of oligosaccharides from lotus (Nelumbo nucifera Gaertn.) seeds. Industrial Crops and Products, 107, 546-557.Machado, I., Faccio, R., & Pistón, M. 2019. Characterization of the effects involved in ultrasound-assisted extraction of trace elements from artichoke leaves and soybean seeds. Ultrasonics Sonochemistry, 59, 104752.Maisarah, A., Amira, N. B., Asmah, R., & Fauziah, O. 2013. Antioxidant analysis of different parts of Carica papaya. International Food Research Journal, 20(3), 1043.Martino, E., Ramaiola, I., Urbano, M., Bracco, F., & Collina, S. 2006. Microwave-assisted extraction of coumarin and related compounds from Melilotus officinalis (L.) Pallas as an alternative to Soxhlet and ultrasound-assisted extraction. Journal of Chromatography A, 1125(2), 147-151.Ming, R., Yu, Q., & Moore, P. 2007. Sex determination in papaya. Seminars in cell & developmental biology, 18, 401-408. doi:10.1016/j.semcdb.2006.11.013Mohammadpour, H., Sadrameli, S. M., Eslami, F., & Asoodeh, A. 2019. Optimization of ultrasound-assisted extraction of Moringa peregrina oil with response surface methodology and comparison with Soxhlet method. Industrial Crops and Products, 131, 106-116. doi: https://doi.org/10.1016/j.indcrop.2019.01.030Nor, M., Manan, Z. A., Mustaffa, A., & Lee, S. 2017. Solubility prediction of flavonoids using new developed UNIFAC-based model. Chemical Engineering Transactions, 56, 799-804.Oreopoulou, A., Tsimogiannis, D., & Oreopoulou, V. 2019. Extraction of polyphenols from aromatic and medicinal plants: an overview of the methods and the effect of extraction parameters. Polyphenols in plants, 243-259.Poureini, F., Mohammadi, M., Najafpour, G. D., & Nikzad, M. 2020. Comparative study on the extraction of apigenin from parsley leaves (Petroselinum crispum L.) by ultrasonic and microwave methods. Chemical Papers, 74(11), 3857-3871.Rabska, M., Pers-Kamczyc, E., Żytkowiak, R., Adamczyk, D., & Iszkuło, G. 2020. Sexual Dimorphism in the Chemical Composition of Male and Female in the Dioecious Tree, Juniperus communis L., Growing under Different Nutritional Conditions. Int J Mol Sci, 21(21). doi:10.3390/ijms21218094Radoiu, M., Splinter, S., & Popek, T. 2019. Continuous industrial-scale microwave-assisted extraction of high-value ingredients from natural biomass. Paper presented at the AMPERE 2019. 17th International Conference on Microwave and High Frequency Heating.Rasul, M. G. 2018. Conventional Extraction Methods Use in Medicinal Plants, their Advantages and Disadvantages. Int J Basic Sciences App Computing, 2(6), 10-14.Sarker, M. M. R., Khan, F., & Mohamed, I. N. 2021. Dengue Fever: Therapeutic Potential of Carica papaya L. Leaves. Frontiers in pharmacology, 12, 610912-610912. doi:10.3389/fphar.2021.610912Satari, A., Ghasemi, S., Habtemariam, S., Asgharian, S., & Lorigooini, Z. 2021. Rutin: A Flavonoid as an Effective Sensitizer for Anticancer Therapy; Insights into Multifaceted Mechanisms and Applicability for Combination Therapy. Evidence-Based Complementary and Alternative Medicine, 2021, 9913179. doi:10.1155/2021/9913179See, T. Y., Tee, S. I., Ang, T. N., Chan, C.-H., Yusoff, R., & Ngoh, G. C. 2016. Assessment of Various Pretreatment and Extraction Methods for the Extraction of Bioactive Compounds from Orthosiphon stamineus Leaf via Microstructures Analysis. International Journal of Food Engineering, 12(7), 711-717. doi:doi:10.1515/ijfe-2016-0094Ying, Z., Han, X., & Li, J. 2011. Ultrasound-assisted extraction of polysaccharides from mulberry leaves. Food Chemistry, 127(3), 1273-1279.Zhang, Q.-W., Lin, L.-G., & Ye, W.-C. 2018. Techniques for extraction and isolation of natural products: A comprehensive review. Chinese medicine, 13(1), 1-26.